Eliminate the Noisy Neighbor Problem in Docker using Resource Limits - Pallavi Priya Patharlagadda (North American Journal of Engineering Research, 2022)
Container technologies are highly popular these days. It is evident that a wide range of applications are operating in containers. Its increased computing usage due to resource sharing and/or isolation is one of the main causes for its widespread adoption. Sharing resources is important, but a careless setup can result in a noisy neighbor scenario. A noisy neighbor scenario incomputing is when a process or collection of processes uses up too many resources on a host. This condition has an adverse effect on other processes that are operating on the same host. In the end, the host's low resources cause it to become less responsive, which lowers the performance of the entire system. This paper will go over how to reduce the noisy neighbor issuein Docker by setting memory and CPU restrictions.